mTOR pathway inhibition alters proliferation as well as differentiation of neural stem cells - Romanyuk, Nataliya; Sintakova, Kristyna; Arzhanov, Ivan; Horak, Martin; Gandhi, Chirag; Jhanwar-Uniyal, Meena; Jendelova, Pavla (Frontiers in Cellular Neuroscience, 2024)
Neural stem cells (NSCs) are essential for both embryonic development and adult neurogenesis, and their dysregulation causes a number of neurodevelopmental disorders, such as epilepsy and autism spectrum disorders. NSC proliferation and differentiation in the developing brain is a complex process controlled by various intrinsic and extrinsic stimuli. The mammalian target of rapamycin (mTOR) regulates proliferation and differentiation, among other cellular functions, and disruption in the mTOR pathway can lead to severe nervous system development deficits. In this study, we investigated the effect of inhibition of the mTOR pathway by rapamycin (Rapa) on NSC proliferation and differentiation. The NSC cultures were treated with Rapa for 1, 2, 6, 24, and 48 hours. The effect on cellular functions was assessed by immunofluorescence staining, western blotting, and proliferation/metabolic assays. mTOR inhibition suppressed NSC proliferation/metabolic activity as well as S-Phase entry by as early as 1 hour of Rapa treatment and this effect persisted up to 48h of Rapa treatment. In a separate experiment, NSCs were differentiated for 2 weeks after treatment with Rapa for 24 or 48 hours. Regarding the effect on neuronal and glial differentiation (2 weeks posttreatment), this was suppressed in NSCs deficient in mTOR signaling, as evidenced by downregulated expression of NeuN, MAP2, and GFAP. We assume that the prolonged effect of mTOR inhibition is realized due to the effect on cytoskeletal proteins. Here, we demonstrate for the first time that the mTOR pathway not only regulates NSC proliferation but also plays an important role in NSC differentiation into both neuronal and glial lineages.